Thromboangiitis Obliterans (Buerger’s disease): A Case Report - Oli, Aadhar; Poudel, Shila; Pandey, Sandeep Raj (Annapurna Journal of Health Sciences, 2023)
Thromboangiitis obliterans (TAO) is an occlusive vascular disease characterized by segmental nonatherosclerotic inflammatory disorder of the small and medium arteries, veins, and nerves of the upper and lower extremities. Also known as Buerger’s disease it is frequently found in men who smoke. Tobacco smoking is central to the initiation and progression of the disease. Here we present a case of a 56- years-old male smoker with complaints of numbness, pain, and discoloration of digits in his right leg for 1 year.